Silicon-carbon composite material for lithium ion battery negative electrode, preparation method thereof, lithium ion battery negative electrode sheet and lithium ion battery

CN122992047APending Publication Date: 2026-10-27LANXI ZHIDE ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611469811.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]然而,现有硅碳复合材料对“硅膜有多厚、碳壁有多厚、硅被限域到什么程度、硅畴与碳畴如何空间排布”等决定材料性能的关键几何信息,长期停留在定性描述,缺乏可量化、可表征、可复现的尺寸界定

Benefits of technology

本发明提供的一种锂离子电池负极用硅碳复合材料,所述硅碳复合材料通过将限域比Rc控制在0.05~0.9范围内,使硅膜厚度与碳骨架孔壁厚度之间形成合理的厚度匹配关系,既为硅的体积膨胀提供了足够的限域空间,又避免了硅膜过厚导致的应力集中与结构破坏。同时,通过将硅畴间距λSi控制在1~200nm范围内,并使λSi/λC≥1.5,使得相邻硅富集畴之间的碳骨架区域能够有效缓冲单个硅畴的体积膨胀应力,防止应力场叠加引发碳骨架开裂,实现硅畴之间的应力解耦。通过将碳畴尺寸λC控制在0.35~40nm范围内,并使tw/λC控制在0.5~1范围内,使得碳骨架在微观尺度上兼具足够的力学支撑强度和结构柔韧性,避免碳畴过小导致的支撑不足或碳畴过大导致的脆性断裂。因此,本发明上述几何参数及其协同关系的共同限定,使硅碳复合材料在硅含量较高的情况下仍能有效抑制体积膨胀效应,提升循环稳定性和首次库伦效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992047A_ABST
    Figure CN122992047A_ABST
Patent Text Reader

Abstract

The application provides a silicon-carbon composite material for a lithium ion battery negative electrode, a preparation method of the silicon-carbon composite material, a lithium ion battery negative electrode sheet and a lithium ion battery, and relates to the technical field of lithium ion batteries. c = Si / w Control is made in 0.05~0.9, so that the silicon film thickness and the hole wall thickness form a reasonable match, which provides a limited space and avoids stress concentration; meanwhile, stress decoupling between silicon domains is realized through λ Si / λ C ≥1.5, stress field superposition is prevented, t w / λ C is limited to satisfy 0.5≤t w / λ C ≤1, so that the carbon skeleton has mechanical support and structural flexibility. Through the synergistic effect of the above-mentioned geometric parameters, the composite material can effectively inhibit volume expansion at a high silicon content, and the cycle stability and the first coulomb efficiency are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a silicon-carbon composite material for lithium-ion battery anodes, a method for preparing the same, a lithium-ion battery anode sheet, and a lithium-ion battery. Background Technology

[0002] Silicon-based anodes have attracted much attention due to their high theoretical specific capacity (approximately 4200 mAh / g), but the approximately 300% volume expansion of silicon during alloying can lead to particle pulverization and interface failure. Confining silicon within the pores of a porous carbon framework using chemical vapor deposition (CVD), utilizing the carbon walls to provide mechanical constraint and a conductive network, is one of the mainstream technical approaches in the industry today.

[0003] However, existing silicon-carbon composite materials have long relied on qualitative descriptions of key geometric information that determines material properties, such as the thickness of the silicon film, the thickness of the carbon wall, the degree to which silicon is confined, and the spatial arrangement of silicon and carbon domains. This lack of quantifiable, characterizable, and reproducible dimensional definitions is problematic. Since the volume expansion of silicon is determined by geometric parameters at various scales, macroscopic parameters such as process temperature, time, and gas flow rate alone cannot guarantee a consistent confinement and buffering effect for materials from different batches and sources of carbon frameworks, thus limiting the stability and controllability of product performance.

[0004] Therefore, there is an urgent need to research and develop a silicon-carbon composite material and its preparation method that is limited by geometric and microstructural dimensions and whose parameters are measurable and verifiable, so as to improve the controllability and consistency of material properties.

[0005] In view of this, the present invention is hereby proposed. Summary of the Invention

[0006] It should be noted that the definitions and test methods for equivalent hole wall thickness, equivalent silicon film thickness, confinement ratio, silicon domain spacing, and carbon domain size in this application are as follows: 1. Equivalent hole wall thickness, symbol t w The unit is nm, which refers to the average thickness of the solid carbon wall between adjacent pores; The equivalent hole wall thickness t w After three-dimensional reconstruction by FIB-SEM or nano-CT, the voxel thickness of the carbon solid wall between adjacent cavities is statistically analyzed and the volume-weighted average value is obtained; or it can be obtained by statistical analysis using the line intercept method on a two-dimensional cross section.

[0007] 2. Equivalent silicon film thickness, symbol t Si The unit is nm, which refers to the equivalent average thickness of the silicon layer deposited on the inner surface of the hole wall; The equivalent silicon film thickness t Si From silicon mass m Si With the inner surface area S of the hole wall int The conversion yields the formula t.Si =m Si / (ρ Si ·S int ), where ρ Si The density of silicon; or obtained by statistically analyzing the average thickness of the silicon layer using TEM-EELS / EDS line scanning.

[0008] 3. Limitation ratio R c The confinement ratio R c For the equivalent silicon film thickness t Si With equivalent hole wall thickness t w The ratio, i.e., R c =t Si / t w , dimensionless, reflects the thickness ratio of the silicon film relative to the pore wall.

[0009] 4. The silicon domain spacing λ Si By identifying continuous regions with silicon atom fractions higher than a preset threshold as silicon domains, the average Euclidean distance between the centroids of adjacent silicon domains is obtained; wherein, the preset threshold is a silicon atom molar fraction ≥ 50%, and silicon-rich regions are identified based on the grayscale threshold of EDS surface scanning or TEM-EELS elemental distribution maps to ensure the reproducibility of silicon domain identification.

[0010] 5. The carbon domain size λ C The characteristics of graphite domains were obtained by analyzing the coherence lengths of the 2D and G peaks in Raman spectroscopy, by analyzing the coherence lengths of small-angle X-ray scattering (SAXS), or by statistically analyzing the characteristic dimensions of graphite domains using high-resolution transmission electron microscopy (HRTEM).

[0011] The definitions and testing methods of the above parameters constitute a unified characterization benchmark defined by this invention, ensuring that materials obtained from carbon skeletons of different batches and sources have consistent and reproducible geometric and microstructure definitions, thereby supporting a reliable evaluation of the effects of the confinement buffering, scale decoupling and scale matching techniques of this invention.

[0012] The first objective of this invention is to provide a silicon-carbon composite material for lithium-ion battery anodes. This silicon-carbon composite material for lithium-ion battery anodes can effectively suppress volume expansion and improve cycle stability and first coulombic efficiency at high silicon content by synergistically controlling the confinement ratio, silicon domain spacing and carbon domain size.

[0013] The second objective of this invention is to provide a method for preparing the silicon-carbon composite material for the negative electrode of a lithium-ion battery.

[0014] A third objective of this invention is to provide a lithium-ion battery negative electrode sheet.

[0015] The fourth objective of this invention is to provide a lithium-ion battery.

[0016] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: This invention provides a silicon-carbon composite material for lithium-ion battery negative electrodes. The silicon-carbon composite material comprises a porous carbon framework and silicon deposited on the inner surface of the pore walls of the porous carbon framework. The composite material satisfies the following conditions: (a) Confinement ratio R c =t Si / t w Satisfying 0.05≤R c ≤0.9; Among them, t w The equivalent pore wall thickness refers to the average thickness of the solid carbon wall between adjacent pores; t Si Equivalent silicon film thickness refers to the average thickness of the silicon layer deposited on the inner surface of the hole wall; (b) Silicon domain spacing λ Si , satisfying 1≤λ Si ≤200nm, the λ Si The average Euclidean distance between the centroids of adjacent silicon enrichment domains; (c) Carbon domain size λ C The condition 0.35 ≤ λ is satisfied. C ≤40nm, the λ C The characteristic size of graphite-like coherent domains in the carbon framework; The silicon domain spacing and carbon domain size satisfy λ. Si / λ C ≥1.5, and the equivalent pore wall thickness and carbon domain size satisfy 0.5≤t w / λ C ≤1.

[0017] Furthermore, the equivalent hole wall thickness t w The thickness is 1~20nm; And / or, the equivalent silicon film thickness t Si The thickness is 0.5~12nm; And / or, the limiting ratio R c Satisfying 0.05≤R c ≤0.7.

[0018] Furthermore, the raw materials for preparing the porous carbon framework are selected from at least one of hard carbon, soft carbon, mesoporous carbon, biomass-derived carbon, resin-derived carbon, pitch-derived carbon, graphite, and Ketjen black. And / or, the specific surface area of ​​the porous carbon framework is 50 m² / g to 2500 m² / g, and the pore volume is 0.2 cm³ / g to 3.0 cm³ / g.

[0019] Furthermore, the silicon mass fraction in the silicon-carbon composite material is 5 wt% to 90 wt%. And / or, the silicon-carbon composite material further includes a doping element selected from at least one of N, B, P, O, S, F, Al, Ti, Mg, Ca and transition metals.

[0020] Furthermore, the outer surface of the porous carbon skeleton is also covered with a coating layer; And / or, the thickness of the coating layer is 0.5~50nm; And / or, the coating layer is a carbon coating layer, which is an amorphous carbon layer, a graphitized carbon layer, or a composite layer of both.

[0021] The present invention provides a method for preparing the above-mentioned silicon-carbon composite material, the method comprising: (A) Provide a porous carbon framework, and then place the porous carbon framework in a closed reactor and introduce a mixture of silicon precursor gas; (B) At a deposition temperature of 300~700℃, silicon is deposited on the inner surface of the pore walls of the porous carbon framework by chemical vapor deposition. The chemical deposition conditions are controlled so that the resulting silicon-carbon composite material satisfies: 0.05≤R c ≤0.9, 1≤λ Si ≤200nm, 0.35≤λ C ≤40nm, λ Si / λ C ≥1.5 and 0.5≤t w / λ C ≤1.

[0022] Furthermore, in (A), the silicon-containing precursor mixed gas is formed by mixing the silicon-containing precursor with a carrier gas; And / or, the silicon-containing precursor is selected from one or more of silane, dichlorosilane, trichlorosilane, and silicon tetrachloride; And / or, the carrier gas is an inert gas, preferably Ar or N2; And / or, the volume fraction of the silicon-containing precursor in the silicon-containing precursor mixture is 5% to 40%, and the system pressure is 10 to 110 kPa.

[0023] Furthermore, the chemical vapor deposition is performed using a segmented temperature control method, including the following steps: First stage: Heat the reactor to 500~650℃, introduce a mixed gas containing silicon precursor, and deposit it for 10~60 min under normal pressure or slight negative pressure of 80~101kPa. Second stage: Cool the reactor to 400~500℃, reduce the system pressure to 10~50kPa, and deposit for 30~120min; The third stage: Heat the reactor to 550~700℃ and anneal it under an inert atmosphere for 30~120 minutes.

[0024] The present invention provides a lithium-ion battery negative electrode sheet, comprising a current collector and a negative electrode active material layer coated on the surface of the current collector, wherein the negative electrode active material layer comprises the silicon-carbon composite material described above, a binder, and an optional conductive agent.

[0025] The present invention provides a lithium-ion battery, which includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode is the negative electrode sheet of the lithium-ion battery of the present invention.

[0026] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention provides a silicon-carbon composite material for lithium-ion battery anodes, wherein the silicon-carbon composite material achieves a confinement ratio R... c By controlling the thickness within the range of 0.05 to 0.9, a reasonable thickness matching relationship is achieved between the silicon film thickness and the carbon framework pore wall thickness. This provides sufficient confinement space for silicon volume expansion while avoiding stress concentration and structural damage caused by excessive silicon film thickness. Simultaneously, by controlling the silicon domain spacing λ... Si Controlled within the range of 1~200nm, and λ Si / λ C A carbon domain size ≥1.5 allows the carbon framework region between adjacent silicon-rich domains to effectively buffer the volume expansion stress of individual silicon domains, preventing stress field superposition from causing cracking of the carbon framework and achieving stress decoupling between silicon domains. C Controlled within the range of 0.35~40nm, and t w / λ C By controlling the parameters within the range of 0.5 to 1, the carbon framework possesses both sufficient mechanical support strength and structural flexibility at the microscale, avoiding insufficient support due to excessively small carbon domains or brittle fracture due to excessively large carbon domains. Therefore, the combined limitation of the aforementioned geometric parameters and their synergistic relationship in this invention enables the silicon-carbon composite material to effectively suppress the volume expansion effect and improve cycle stability and initial coulombic efficiency even with high silicon content.

[0027] This invention provides a method for preparing a silicon-carbon composite material. The method involves placing a porous carbon skeleton in a closed reactor and introducing a silicon-containing precursor gas mixture. Chemical vapor deposition (CVD) is then performed at a deposition temperature of 300–700°C, causing silicon to preferentially deposit on the inner surface of the pore walls of the porous carbon skeleton rather than on the outer surface or pore openings, thereby forming a microstructure in which the silicon phase is confined and encapsulated by the carbon skeleton. By controlling the CVD conditions, the resulting silicon-carbon composite material satisfies 0.05 ≤ R. c ≤0.9, 1≤λ Si ≤200nm, 0.35≤λ C ≤40nm, λ Si / λ C ≥1.5 and 0.5≤tw / λ C ≤1 means that by adjusting process parameters such as deposition temperature, precursor concentration, system pressure and deposition time, the equivalent pore wall thickness, equivalent silicon film thickness, confinement ratio, silicon domain spacing and carbon domain size can be synergistically controlled, thereby preparing silicon-carbon composite materials with confinement buffer, scale decoupling and scale matching characteristics, and obtaining excellent comprehensive electrochemical performance.

[0028] This invention provides a lithium-ion battery anode sheet, wherein the anode active material layer of the lithium-ion battery anode sheet comprises the aforementioned silicon-carbon composite material. Based on the characteristics of the silicon-carbon composite material of this invention, where silicon is confined within the inner surface of the porous carbon framework pore walls and the geometric parameters are synergistically matched, this lithium-ion battery anode sheet can effectively suppress the volume expansion effect of silicon during charging and discharging, thereby achieving better electrochemical performance.

[0029] This invention provides a lithium-ion battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode is the aforementioned lithium-ion battery negative electrode sheet of this invention. By applying the lithium-ion battery negative electrode sheet of this invention to a lithium-ion battery, the energy density, cycle stability, and rate performance of the lithium-ion battery are all improved. Attached Figure Description

[0030] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0031] Figure 1 A schematic diagram of the geometric structure of the silicon-carbon composite material for the negative electrode of a lithium-ion battery provided by the present invention; Figure 2 The image shows a TEM-HAADF image of the silicon-carbon structure of the silicon-carbon composite material provided in Example 1 of this invention. Detailed Implementation

[0032] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] According to one aspect of the present invention, a silicon-carbon composite material for a lithium-ion battery negative electrode, the silicon-carbon composite material comprising a porous carbon framework and silicon deposited on the inner surface of the pore walls of the porous carbon framework, the composite material satisfying the following conditions: (a) Confinement ratio R c =t Si / t w Satisfying 0.05≤R c ≤0.9; Among them, t w The equivalent pore wall thickness refers to the average thickness of the solid carbon wall between adjacent pores; t Si Equivalent silicon film thickness refers to the average thickness of the silicon layer deposited on the inner surface of the hole wall; (b) Silicon domain spacing λ Si , satisfying 1≤λ Si ≤200nm, the λ Si The average Euclidean distance between the centroids of adjacent silicon enrichment domains; (c) Carbon domain size λ C The condition 0.35 ≤ λ is satisfied. C ≤40nm, the λ C The characteristic size of graphite-like coherent domains in the carbon framework; The silicon domain spacing and carbon domain size satisfy λ. Si / λ C ≥1.5, and the equivalent pore wall thickness and carbon domain size satisfy 0.5≤t w / λ C ≤1.

[0034] This invention provides a silicon-carbon composite material for lithium-ion battery anodes, wherein the silicon-carbon composite material achieves a confinement ratio R... c By controlling the thickness within the range of 0.05 to 0.9, a reasonable thickness matching relationship is achieved between the silicon film thickness and the carbon framework pore wall thickness. This provides sufficient confinement space for silicon volume expansion while avoiding stress concentration and structural damage caused by excessive silicon film thickness. Simultaneously, by controlling the silicon domain spacing λ... Si Controlled within the range of 1~200nm, and λ Si / λ C A carbon domain size ≥1.5 allows the carbon framework region between adjacent silicon-rich domains to effectively buffer the volume expansion stress of individual silicon domains, preventing stress field superposition from causing cracking of the carbon framework and achieving stress decoupling between silicon domains. C Controlled within the range of 0.35~40nm, and t w / λ CBy controlling the parameters within the range of 0.5 to 1, the carbon framework possesses both sufficient mechanical support strength and structural flexibility at the microscale, avoiding insufficient support due to excessively small carbon domains or brittle fracture due to excessively large carbon domains. Therefore, the combined limitation of the aforementioned geometric parameters and their synergistic relationship in this invention enables the silicon-carbon composite material to effectively suppress the volume expansion effect and improve cycle stability and initial coulombic efficiency even with high silicon content.

[0035] In a preferred embodiment of the present invention, the equivalent hole wall thickness t w The thickness is 1~20nm; and / or, the equivalent silicon film thickness t Si The thickness is 0.5~12nm; As a preferred embodiment, the present invention uses an equivalent hole wall thickness t w The thickness is limited to 1-20 nm to ensure the carbon framework pore walls have sufficient mechanical strength to withstand the volume expansion stress of silicon, while avoiding excessively thick pore walls that would reduce the effective silicon storage space and lengthen the lithium-ion transport path, thus balancing cycle stability and rate performance. Si By limiting the thickness to 0.5~12nm, silicon is uniformly attached to the inner surface of the pore wall in the form of a continuous nano-thin layer, which not only ensures a high silicon loading and reversible capacity, but also avoids confinement failure and cyclic pulverization caused by excessively thick silicon films.

[0036] Figure 1 This is a schematic diagram of the geometric structure of the silicon-carbon composite material for the negative electrode of a lithium-ion battery provided by the present invention.

[0037] in, Figure 1 (a) is a cross-sectional schematic diagram of the overall geometric structure of silicon-carbon composite material, showing the morphology of silicon film deposited on the inner surface of the porous carbon skeleton pore wall and silicon domains dispersed in the carbon skeleton, which is used to illustrate the confined structure feature of "silicon deposited on the inner surface of the pore wall" in this invention. Figure 1 In (b), the limiting ratio R is... c =t Si / t w The illustration shows the silicon film thickness t Si The matching relationship between the silicon film thickness and the carbon wall thickness tw is used to illustrate the technical effect of the present invention of "reasonable matching between silicon film thickness and carbon wall thickness"; Figure 1 In the middle (c), the silicon domain spacing λ is represented. Si With carbon domain size λ C Spatial layout diagram, showing λ Si / λ C A stress decoupling relationship of ≥1.5 is used to illustrate the technical effect of the present invention that "the silicon domain spacing is greater than the carbon domain size to avoid stress coupling".

[0038] To fully understand the meaning and synergistic effect of the geometric and microstructural dimensional features described above in this invention, the physical meaning of each parameter, the basis for setting the corresponding numerical range, and the beneficial effects obtained when the parameter values ​​fall within the above range will be explained below.

[0039] (1) Equivalent hole wall thickness t w (1nm≤t) w ≤20nm): Physical meaning: t w The average thickness of the solid carbon wall between adjacent cavities is the main mechanical load-bearing unit of the composite material to withstand the volume expansion of silicon alloying, and also serves as a continuous framework for electron conduction. w The larger the volume, the more carbon atoms that can buffer expansion within a unit volume; t w The smaller the hole, the thinner and more brittle the hole wall.

[0040] Limitation basis: when t w When the diameter is <1nm, the hole wall is too thin and the mechanical strength is insufficient. The hole wall is prone to fracture during silicon expansion, resulting in loss of the confinement buffer effect and interruption of the electron pathway; when t w When the thickness exceeds 20nm, the carbon wall occupies too much volume, reducing the effective silicon storage space and resulting in low silicon loading. Furthermore, the path for lithium ions to traverse the thick wall becomes longer, significantly increasing transport impedance and deteriorating rate performance. Therefore, t w Limited to 1~20nm.

[0041] Beneficial effects: Compared with existing undefined t w Compared to other materials, t w A depth of 1-20 nm ensures that the pore walls provide sufficient mechanical buffering without sacrificing capacity and dynamics due to excessive thickness, thus balancing cycle stability and rate performance.

[0042] (2) Equivalent silicon film thickness t Si (0.5nm≤t) Si ≤12nm): Physical meaning: t Si t represents the equivalent average thickness of the silicon layer deposited on the inner surface of the aperture wall, indicating the silicon loading per unit aperture wall area. Si The thinner the layer, the more the silicon is confined by the carbon walls in a nanometer-thin layer; t Si The thicker the silicon domain, the larger its volume and the higher its expansion strain.

[0043] Limitation basis: when t Si At a wavelength <0.5nm, the silicon layer is discontinuous and island-like, reducing reversible lithium intercalation sites and decreasing both initial efficiency and reversible capacity; when t Si When the silicon thickness exceeds 12 nm, the single-domain silicon thickness surpasses the critical size that can be accommodated by thin-walled plasticity, leading to carbon wall confinement failure. Silicon expansion then results in localized high stress concentrations and cyclic pulverization. Therefore, t... SiLimited to 0.5~12nm.

[0044] Beneficial effects: Compared with existing over-deposited or under-deposited materials, t Si Falling into a 0.5~12nm layer keeps silicon as a continuous thin layer confined by carbon walls, maintaining low expansion, high first efficiency and long cycle life while maintaining high silicon content.

[0045] (3) Limitation ratio R c =t Si / t w (0.05≤R) c ≤0.9): Physical meaning: R c R is the ratio of silicon film thickness to hole wall thickness, a dimensionless "load / force" ratio that directly expresses the degree to which the carbon wall confines silicon expansion. c The smaller the value, the thicker the carbon wall and the greater the buffer margin; R c The larger the value, the heavier the silicon load.

[0046] Limitation basis: When R c When R < 0.05, the silicon loading is too low and the capacity is meaningless; when R c When the silicon film thickness is greater than 0.9, the silicon film thickness approaches or exceeds the hole wall thickness, the carbon wall can no longer provide an effective confinement, and the silicon expansion extrapolates and destroys the structure.

[0047] Beneficial effects: Compared with existing materials that do not control this ratio and often exhibit "silicon-filled cavities" or "excessively thick silicon films," R... c Limiting the carbon wall to 0.05~0.9 ensures that it remains in a position to absorb silicon expansion, which constitutes the core of the confined buffering effect of this invention.

[0048] (4) Silicon domain spacing λ Si (1nm≤λ) Si ≤200nm): Physical meaning: λ Si λ represents the average Euclidean distance between the centroids of adjacent silicon-rich domains, reflecting the spatial density of the silicon phase distribution. Si The larger the value, the more dispersed the silicon domains; λ Si The smaller the size, the denser the silicon domains form a network.

[0049] Limitation basis: when λ Si When the wavelength is <5nm, adjacent silicon domains are closely coupled, and their expansion strain fields superimpose, forming large stress concentrations locally and disrupting the conductive network; when λ Si At wavelengths greater than 200 nm, silicon domains become excessively isolated, their electronic connectivity deteriorates, leading to decreased utilization of active silicon and uneven local current distribution. Therefore, λ... Si Limited to 1~200nm.

[0050] Beneficial effects: Compared with existing materials where the silicon phase distribution is irregular and often exhibits localized over-density, λ Si Falling into the 1~200nm range decouples the expansion fields of each silicon domain from each other, maintaining electron percolation connectivity while avoiding superimposed stress.

[0051] (5) Carbon domain size λ C (0.35nm≤λ) C ≤40nm): Physical meaning: λ C λ represents the characteristic size of graphite-like coherent domains in the carbon framework, reflecting the crystallinity and flexibility of carbon. C The smaller the value, the more amorphous it tends to be, the better its flexibility, but the weaker its electrical conductivity; λ C The larger the size, the more graphitized it becomes, the better its electrical conductivity, but the higher its brittleness.

[0052] Limitation basis: when λ C At wavelengths < 2 nm, carbon is too disordered, resulting in poor electronic conductivity and insufficient structural strength; when λ... C At wavelengths greater than 40 nm, the crystallinity is too high, the flexibility is extremely poor, and the material's internal structure cannot provide sufficient deformation tolerance, making it difficult for the carbon framework to buffer and accommodate silicon expansion. Therefore, λ... C Limited to 0.35~40nm.

[0053] Beneficial effects: Compared with existing carbon frameworks that are not crystallinity-controlled or are over-graphitized, λ C Achieving a balance between electron conduction and structural flexibility within the range of 0.35~40nm allows the carbon framework to conduct electrons and absorb stress through moderate deformation during silicon expansion.

[0054] In summary, the aforementioned technical features and parameters of this application are not isolated, but rather derived through R... c =t Si / t w Intrinsic constraints, λ Si / λ C Decoupling relationship ≥1.5, t w / λ C Satisfying 0.5≤t w / λ C The ≤1 scale matching forms a synergy: the carbon wall confined thin silicon film and the silicon domain spacing larger than the carbon domain size to avoid stress coupling, together achieve the unity of high first efficiency, high reversible capacity, long cycle life and excellent rate performance.

[0055] Preferably, the confinement ratio R c Satisfying 0.05≤R c ≤0.7.

[0056] Preferably, the composite material satisfies the following conditions: (a) The confinement ratio Rc = tSi / tw satisfies 0.20 ≤ Rc ≤ 0.67; Where tw is the equivalent hole wall thickness, which refers to the average thickness of the carbon solid wall between adjacent holes; tSi is the equivalent silicon film thickness, which refers to the average thickness of the silicon layer deposited on the inner surface of the hole wall. (b) The silicon domain spacing λSi satisfies 24.5nm≤λSi≤66nm; where λSi is the average Euclidean distance between the centroids of adjacent silicon-rich domains. (c) The carbon domain size λC satisfies 7nm≤λC≤18nm; λC is the characteristic size of the graphite-like coherent domain in the carbon skeleton; the silicon domain spacing and the carbon domain size satisfy λSi / λC≥2.9, and the equivalent pore wall thickness and the carbon domain size satisfy 0.5≤tw / λC≤0.83. In a preferred embodiment of the present invention, the raw material for preparing the porous carbon skeleton is selected from at least one of hard carbon, soft carbon, mesoporous carbon, biomass-derived carbon, resin-derived carbon, pitch-derived carbon, graphite, and Ketjen black.

[0057] In a preferred embodiment of the present invention, the porous carbon framework has a specific surface area of ​​50 m² / g to 2500 m² / g and a pore volume of 0.2 cm³ / g to 3.0 cm³ / g.

[0058] In a preferred embodiment, this invention limits the specific surface area of ​​the porous carbon framework to 50 m² / g to 2500 m² / g, ensuring sufficient inner surface area of ​​the pore walls for silicon deposition. This avoids insufficient silicon deposition space due to an excessively low specific surface area, or excessively high surface area resulting in thin pore walls and reduced mechanical strength. By limiting the pore volume to 0.2 cm³ / g to 3.0 cm³ / g, the carbon framework has sufficient porosity to accommodate silicon deposition and volume expansion, while avoiding excessively large pore volumes that would lead to a loose carbon framework structure and discontinuous electron conduction paths. This synergistic limitation of specific surface area and pore volume provides a suitable porous carbon framework structural basis for the subsequent uniform confined deposition of silicon.

[0059] Preferably, the porosity of the porous carbon skeleton is 30% to 70%.

[0060] In a preferred embodiment of the present invention, the silicon mass fraction in the silicon-carbon composite material is 5wt% to 90wt%.

[0061] In a preferred embodiment of the present invention, the silicon-carbon composite material further includes a doping element selected from at least one of N, B, P, O, S, F, Al, Ti, Mg, Ca and transition metals.

[0062] As a preferred embodiment, the present invention introduces the above-mentioned doping elements into silicon-carbon composite materials, thereby controlling the electronic structure of silicon and / or carbon by the doping elements, improving the electronic conductivity of silicon-carbon composite materials, improving the diffusion kinetics of lithium ions, and enhancing the interfacial bonding force between silicon and carbon skeleton, thereby further improving the first coulombic efficiency, rate performance and cycle stability.

[0063] In a preferred embodiment of the present invention, the outer surface of the porous carbon skeleton is further covered with a coating layer; And / or, the thickness of the coating layer is 0.5~50nm; And / or, the coating layer is a carbon coating layer, which is an amorphous carbon layer, a graphitized carbon layer, or a composite layer of both.

[0064] According to one aspect of the present invention, a method for preparing the above-mentioned silicon-carbon composite material, the method comprising: (A) Provide a porous carbon framework, and then place the porous carbon framework in a closed reactor and introduce a mixture of silicon precursor gas; (B) At a deposition temperature of 300~700℃, silicon is deposited on the inner surface of the pore walls of the porous carbon framework by chemical vapor deposition. The chemical deposition conditions are controlled so that the resulting silicon-carbon composite material satisfies: 0.05≤R c ≤0.9, 1≤λ Si ≤200nm, 0.35≤λ C ≤40nm, λ Si / λ C ≥1.5 and 0.5≤t w / λ C ≤1.

[0065] This invention provides a method for preparing a silicon-carbon composite material. The method involves placing a porous carbon skeleton in a closed reactor and introducing a silicon-containing precursor gas mixture. Chemical vapor deposition (CVD) is then performed at a deposition temperature of 300–700°C, causing silicon to preferentially deposit on the inner surface of the pore walls of the porous carbon skeleton rather than on the outer surface or pore openings, thereby forming a microstructure in which the silicon phase is confined and encapsulated by the carbon skeleton. By controlling the CVD conditions, the resulting silicon-carbon composite material satisfies 0.05 ≤ R. c ≤0.9, 1≤λ Si ≤200nm, 0.35≤λ C ≤40nm, λ Si / λ C ≥1.5 and 0.5≤t w / λ C≤1 means that by adjusting process parameters such as deposition temperature, precursor concentration, system pressure and deposition time, the equivalent pore wall thickness, equivalent silicon film thickness, confinement ratio, silicon domain spacing and carbon domain size can be synergistically controlled, thereby preparing silicon-carbon composite materials with confinement buffer, scale decoupling and scale matching characteristics, and obtaining comprehensive performance of high initial coulombic efficiency, high reversible capacity and long cycle life.

[0066] In a preferred embodiment of the present invention, the silicon-containing precursor mixed gas in (A) is formed by mixing the silicon-containing precursor with a carrier gas; And / or, the silicon-containing precursor is selected from one or more of silane, dichlorosilane, trichlorosilane, and silicon tetrachloride; And / or, the carrier gas is an inert gas, preferably Ar or N2; And / or, the volume fraction of the silicon-containing precursor in the silicon-containing precursor mixture is 5% to 40%, and the system pressure is 10 to 110 kPa.

[0067] In a preferred embodiment of the present invention, the chemical vapor deposition is performed using a segmented temperature control method, comprising the following steps: First stage: Heat the reactor to 500-650℃, introduce a mixed gas containing silicon precursor, and deposit for 10-60 minutes under normal pressure or slight negative pressure of 80-101kPa, so that silicon is preferentially deposited on the inner walls of macropores and mesopores of the porous carbon framework. Second stage: Cool the reactor to 400-500℃, reduce the system pressure to 10-50kPa, and continue deposition for 30-120min to allow silicon to be further deposited on the inner walls of the mesopores and pores of the porous carbon framework. The third stage involves heating the reactor to 550–700°C and annealing it under an inert atmosphere for 30–120 minutes to redistribute and relax the deposited silicon, thereby adjusting the silicon domain spacing λ. Si and carbon domain size λ C .

[0068] As a preferred embodiment, the chemical vapor deposition of this invention employs a segmented temperature-controlled method, wherein: in the first stage, the reactor is heated to 500-650°C and deposition is carried out for 10-60 minutes under normal or slightly negative pressure, allowing silicon to preferentially deposit on the inner walls of macropores and mesopores of the porous carbon framework, initially constructing a macroscopic distribution framework for the silicon phase; in the second stage, the reactor is cooled to 400-500°C, the system pressure is reduced to 10-50 kPa, and deposition continues for 30-120 minutes, allowing silicon to be further deposited on the inner walls of mesopores and micropores, achieving gradient filling of silicon in the hierarchical channels; in the third stage, the reactor is heated to 550-700°C and annealed under an inert atmosphere for 30-120 minutes, causing the deposited silicon to redistribute and undergo structural relaxation, adjusting the silicon domain spacing λ. Siand carbon domain size λ C This process optimizes the dispersion uniformity of the silicon phase and the microstructural order of the carbon framework. Through the segmented temperature control process described above, precise control over the silicon deposition depth, distribution uniformity, and scale matching relationship between silicon and carbon domains is achieved, further enhancing the electrochemical performance of silicon-carbon composite materials.

[0069] According to one aspect of the present invention, a lithium-ion battery negative electrode sheet includes a current collector and a negative electrode active material layer coated on the surface of the current collector, the negative electrode active material layer comprising the silicon-carbon composite material described above, a binder, and optionally a conductive agent.

[0070] This invention provides a lithium-ion battery anode sheet, wherein the anode active material layer of the lithium-ion battery anode sheet comprises the aforementioned silicon-carbon composite material. Based on the characteristics of the silicon-carbon composite material of this invention, where silicon is confined within the inner surface of the porous carbon framework pore walls and the geometric parameters are synergistically matched, this lithium-ion battery anode sheet can effectively suppress the volume expansion effect of silicon during charging and discharging, thereby achieving better electrochemical performance.

[0071] According to one aspect of the present invention, a lithium-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode is the negative electrode sheet of the lithium-ion battery of the present invention.

[0072] This invention provides a lithium-ion battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode is the aforementioned lithium-ion battery negative electrode sheet of this invention. By applying the lithium-ion battery negative electrode sheet of this invention to a lithium-ion battery, the energy density, cycle stability, and rate performance of the lithium-ion battery are all improved.

[0073] The technical solution of the present invention will be further described below with reference to the embodiments.

[0074] Example 1 A method for preparing a silicon-carbon composite material for a lithium-ion battery negative electrode includes the following steps: 1. Provides a porous carbon framework: Resin-derived hard carbon was used as a porous carbon framework, with a BET specific surface area of ​​800 m² / g, a pore volume of 1.2 cm³ / g, and a porosity of 61%.

[0075] 2. Placed in a closed reactor: The porous carbon framework described above was loaded into a closed chemical vapor deposition (CVD) reactor. The reactor was then sealed, and after evacuation, high-purity argon gas was repeatedly introduced to replace the internal air and provide an inert gas protective environment.

[0076] 3. Introduce a mixture of gases containing silicon precursors: A silicon precursor mixture is introduced into a closed reactor. The silicon precursor is silane (SiH4), and the carrier gas is high-purity nitrogen (N2). The volume fraction of silane in the mixture is precisely controlled by a mass flow controller to maintain 5% and the system pressure at 95 kPa, while ensuring a continuous and stable gas flow.

[0077] 4. Chemical vapor deposition: The heating system was turned on, and chemical vapor deposition was performed at 550°C for 45 minutes. Throughout the deposition process, the silane partial pressure and residence time were precisely controlled to ensure that silicon preferentially deposited on the inner surface of the pore walls of the porous carbon framework, avoiding excessive accumulation of silicon at the pore openings or outer surfaces. Under these conditions, the active silicon species generated by silane pyrolysis penetrated deep into the internal channels of the porous carbon framework and nucleated and grew uniformly along the pore walls, forming a continuous and adherent silicon film.

[0078] 5. Structural characterization: Figure 2 This is a TEM-HAADF image of the silicon-carbon structure of the silicon-carbon composite material provided in Embodiment 1 of the present invention. Figure 2 The bright areas are silicon domains, and the dark areas are carbon domains.

[0079] The microstructure parameters of the composite material were obtained by SEM, TEM cross-sectional statistics, and XRD characterization as follows:

[0080] Example 2 A method for preparing a silicon-carbon composite material for a lithium-ion battery negative electrode includes the following steps: 1. Provides a porous carbon framework: Biomass-derived mesoporous carbon was used as a porous carbon framework, with a BET specific surface area of ​​650 m² / g, a pore volume of 1.0 cm³ / g, and a porosity of 55%.

[0081] 2. Placed in a closed reactor: Same as in Example 1.

[0082] 3. Introduce a mixture of gases containing silicon precursors: A silicon precursor mixture is introduced into a closed reactor. The silicon precursor is silane (SiH4), and the carrier gas is high-purity nitrogen (N2). The volume fraction of silane in the mixture is precisely controlled by a mass flow controller to maintain 3% and the system pressure at 90 kPa, while ensuring a continuous and stable gas flow.

[0083] 4. Chemical vapor deposition The heating system was turned on, and chemical vapor deposition was performed at 480℃ for 60 minutes. Throughout the deposition process, the silane partial pressure and residence time were precisely controlled to ensure that silicon preferentially deposited on the inner surface of the pore walls of the porous carbon framework, avoiding excessive accumulation of silicon at the pore openings or outer surfaces. Under these conditions, the active silicon species generated by silane pyrolysis penetrated deep into the internal channels of the porous carbon framework and nucleated and grew uniformly along the pore walls, forming a continuous and adherent silicon film.

[0084] 5. Structural Characterization The microstructure parameters of the composite material were obtained by SEM, TEM cross-sectional statistics, and XRD characterization as follows:

[0085] Example 3 (Segmented Temperature-Controlled Deposition) A method for preparing a silicon-carbon composite material for a lithium-ion battery negative electrode includes the following steps: 1. Provide a porous carbon framework: Same as in Example 1.

[0086] 2. Placed in a closed reactor: Same as in Example 1.

[0087] 3. Introduce a mixed gas containing silicon precursors: Same as in Example 1.

[0088] 4. Chemical vapor deposition: A segmented temperature-controlled method is used for chemical vapor deposition. The specific process is as follows: First stage: Heat the reactor to 600℃, introduce a mixed gas containing silicon precursor, and deposit it under normal pressure for 30 minutes; Second stage: Cool the reactor to 450℃, reduce the system pressure to 50kPa, allow deposition for 60min, replenish the deposited surface layer, and adjust the confinement ratio R. c The borehole exhibits a reasonable gradient descent distribution from the orifice to the bottom. Third stage: Heat the reactor to 600℃ and anneal it under an inert atmosphere for 60 minutes.

[0089] Throughout the deposition process, the silane partial pressure and residence time at each stage are precisely controlled to ensure that silicon preferentially deposits on the inner surface of the pore walls of the porous carbon framework, avoiding excessive accumulation of silicon at the pore openings or outer surfaces. Under these conditions, the active silicon species generated by silane pyrolysis penetrate deep into the internal channels of the porous carbon framework and nucleate and grow uniformly along the pore walls, forming a continuously bonded silicon film.

[0090] 5. Structural characterization: The microstructure parameters of the composite material were obtained by SEM, TEM cross-sectional statistics, and XRD characterization as follows:

[0091] Example 4 A method for preparing a silicon-carbon composite material for a lithium-ion battery negative electrode includes the following steps: 1. Provides a porous carbon framework: Moderately graphitized soft carbon was used as a porous carbon framework, with a BET specific surface area of ​​500 m² / g, a pore volume of 0.8 cm³ / g, and a porosity of 52%.

[0092] 2. Placed in a closed reactor: Same as in Example 1.

[0093] 3. Introduce a mixture of gases containing silicon precursors: A silicon precursor mixture was introduced into a closed reactor. The silicon precursor was silane (SiH4), the doping precursor was a phosphorus-containing gas, and the carrier gas was high-purity nitrogen (N2). The volume fraction of silane in the mixture was precisely controlled by a mass flow controller to maintain 20% and 1% of phosphorus in the mixture, while the system pressure was maintained at 95 kPa, and the gas was continuously and steadily introduced.

[0094] 4. Chemical vapor deposition: The heating system was activated, and chemical vapor deposition was performed at 520°C. Throughout the deposition process, the silane partial pressure and residence time were precisely controlled to ensure that silicon preferentially deposited on the inner surface of the pore walls of the porous carbon framework, avoiding excessive accumulation of silicon at the pore openings or outer surfaces. Under these conditions, the active species generated by the decomposition of silane and phosphorus-containing gas penetrated deep into the internal channels of the porous carbon framework and uniformly nucleated and grew along the pore walls, forming a continuous and adherent phosphorus-doped silicon film.

[0095] The phosphorus doping level was determined to be 1.5 at.

[0096] 5. Structural Characterization The microstructure parameters of the composite material were obtained by SEM, TEM cross-sectional statistics, and XRD characterization as follows:

[0097] Example 5 A method for preparing a silicon-carbon composite material for a lithium-ion battery negative electrode includes the following steps: 1. Provides a porous carbon framework: High specific surface area porous carbon was used as the porous carbon framework, with a BET specific surface area of ​​1500 m² / g, a pore volume of 1.5 cm³ / g, and a porosity of 58%.

[0098] 2. Placed in a closed reactor: Same as in Example 1.

[0099] 3. Introduce a mixture of gases containing silicon precursors: A silicon precursor mixture is introduced into a closed reactor. The silicon precursor is silane (SiH4), and the carrier gas is high-purity nitrogen (N2). The volume fraction of silane in the mixture is precisely controlled by a mass flow controller to maintain 15% and the system pressure at 85 kPa, while ensuring a continuous and stable gas flow.

[0100] 4. Chemical vapor deposition: The heating system is activated, and low-partial-pressure slow chemical vapor deposition is performed at 500°C. Throughout the deposition process, the low silane partial pressure and long residence time are precisely controlled to ensure that silicon is deposited slowly and uniformly on the inner surface of the porous carbon framework, avoiding excessive accumulation of silicon at the pore openings or outer surfaces. Under these conditions, the active silicon species generated by silane decomposition penetrate deep into the internal channels of the porous carbon framework and nucleate and grow uniformly along the pore walls, forming a continuous and adherent silicon film.

[0101] 5. Structural characterization: The microstructure parameters of the composite material were obtained by SEM, TEM cross-sectional statistics, and XRD characterization as follows:

[0102] Example 6 The silicon-carbon composite material prepared in Example 1 of this invention is coated with an amorphous carbon layer on its surface using a gas-phase pyrolysis carbon coating method, specifically including the following steps: 1. The silicon-carbon composite material obtained in Example 1 was placed in a tube furnace and heated to 600°C at a rate of 5°C / min under nitrogen protection; 2. Acetylene gas was introduced, and the volume fraction of acetylene in the carrier gas was controlled to be 5%. The gas was then pyrolyzed and deposited at 600℃ for 30 min to form an amorphous carbon coating layer with a thickness of about 2 nm on the outer surface of the porous carbon framework. 3. Allow to cool naturally to room temperature to obtain the silicon-carbon composite material containing the coating layer described in this invention. The coating layer is an amorphous carbon layer.

[0103] 4. Structural characterization: The microstructure parameters of the composite material were obtained by SEM, TEM cross-sectional statistics, and XRD characterization as follows:

[0104] Comparative Example 1 (Thick Silicon Filling) By changing the deposition conditions, silicon is enriched in large quantities within the pores, forming a thick silicon filling.

[0105] A resin-derived hard carbon porous carbon framework (BET specific surface area 800 m² / g, pore volume 1.2 cm³ / g, porosity 61%) identical to that in Example 1 was placed in a closed CVD reactor. A mixture of silane (SiH4) and high-purity nitrogen (N2) was introduced, wherein the volume fraction of silane was 25%, and the system pressure was maintained at 100 kPa.

[0106] The heating system was turned on, and chemical vapor deposition was performed at 600°C for 120 min. By increasing the silane concentration and extending the deposition time, silicon was enriched and over-deposited in the pores, forming a thick silicon-filled structure. After deposition, the product was naturally cooled to room temperature under argon protection and then removed. The remaining post-processing steps were the same as in Example 1.

[0107] Structural characterization: The microstructure parameters of the composite material were obtained by SEM, TEM cross-sectional statistics, and XRD characterization as follows:

[0108] Comparative Example 2 (Silicon Domain Density) The use of a specific highly active carbon source leads to excessive nucleation of silicon deposition.

[0109] Highly active coconut shell activated carbon was used as the porous carbon framework (BET specific surface area 1500 m² / g, pore volume 1.5 cm³ / g, porosity 54%). Its surface is rich in oxygen-containing functional groups and exhibits high reactivity. It was placed in a closed CVD reactor. A mixture of silane (SiH4) and high-purity nitrogen (N2) was introduced, with silane comprising 10% by volume, and the system pressure was maintained at 95 kPa.

[0110] The heating system was turned on, and chemical vapor deposition was performed at 450°C for 90 min. Due to the excessively high density of active sites on the carbon framework surface, silanes excessively nucleated on the pore wall surface, resulting in a dense distribution of silicon domains and excessively small interdomain spacing. After deposition, the product was naturally cooled to room temperature under argon protection and then removed. The remaining post-processing steps were the same as in Example 1.

[0111] Structural characterization: The microstructure parameters of the composite material were obtained by SEM, TEM cross-sectional statistics, and XRD characterization as follows:

[0112] Comparative Example 3 (carbon domain size is too large) The carbon skeleton is treated with ultra-high temperature graphitization at 2800℃, resulting in excessively high crystallinity and extremely poor flexibility.

[0113] A porous carbon framework (BET specific surface area 300 m² / g, pore volume 0.5 cm³ / g, porosity 40%), treated with ultra-high temperature graphitization at 2800℃, was selected. This framework exhibits high graphitization, large carbon domain size, and extremely poor flexibility. It was placed in a closed CVD reactor. A mixture of silane (SiH4) and high-purity nitrogen was introduced, with silane comprising 5% by volume, and the system pressure was maintained at 95 kPa.

[0114] The heating system was turned on, and chemical vapor deposition was performed at 550°C for 45 min. Due to the ultra-high temperature graphitization treatment of the carbon framework at 2800°C, the carbon domain size was too large (approximately 50 nm), and the material lacked sufficient deformation tolerance, making it difficult for the carbon framework to buffer and accommodate silicon expansion. After deposition, the material was naturally cooled to room temperature under argon protection, and the product was removed. The remaining post-processing steps were the same as in Example 1.

[0115] Structural characterization: The microstructure parameters of the composite material were obtained by SEM, TEM cross-sectional statistics, and XRD characterization as follows:

[0116] Comparative Example 4 (Equivalent Hole Wall Thickness Too Large) Large-pore carbon materials with extremely thick solid carbon walls are used as the framework.

[0117] A large-pore carbon material with extremely thick solid carbon walls was used as a porous carbon framework (BET specific surface area 200 m² / g, pore volume 0.3 cm³ / g, porosity 35%, equivalent pore wall thickness approximately 25 nm), and placed in a closed CVD reactor. A mixture of silane (SiH4) and high-purity nitrogen was introduced, with the silane volume fraction being 8%, and the system pressure was maintained at 95 kPa.

[0118] The heating system was turned on, and chemical vapor deposition was performed at 550°C for 60 min to deposit silicon on the inner surface of the pore walls of the thick-walled carbon framework. Due to the excessive thickness of the carbon framework solid walls (25 nm), the lithium-ion transport path was significantly prolonged, and the structural flexibility of the thick-walled carbon was insufficient to effectively buffer the volume expansion of silicon. After deposition, the product was naturally cooled to room temperature under argon protection, and then removed. The remaining post-processing steps were the same as in Example 1.

[0119] Structural characterization: The microstructure parameters of the composite material were obtained by SEM, TEM cross-sectional statistics, and XRD characterization as follows:

[0120] Experiment Example 1: Electrochemical Performance Testing and Comparative Analysis The composite materials from the above examples and comparative examples were used as negative electrode active materials, mixed with PAA binder and Super P conductive agent at a mass ratio of 8:1:1, and coated onto copper foil to prepare electrode sheets. Using lithium metal sheets as counter electrodes, CR2032 coin cell half-cells were assembled. Charge-discharge tests were conducted at 0.1C rate to obtain initial efficiency and specific capacity, followed by 100-cycle tests at 1C rate. The test results are shown in Tables 1 and 2. Table 1. Summary of process structure data for each embodiment and comparative example:

[0121] Table 2 Summary of electrochemical performance data for each example and comparative example:

[0122] As shown in Tables 1 and 2, Examples 1-5 all exhibit excellent electrochemical performance. Examples 1-3, with silicon contents of 35wt%-45wt%, show an initial efficiency ≥85%, a 100-cycle 1C capacity retention ≥90%, and a full-charge expansion ≤64%. Example 4, with a higher silicon content of 60wt%, shows an initial efficiency of 93.5%, a 100-cycle 1C capacity retention of 90.2%, and a full-charge expansion of 110%. Example 5, with a silicon content of 38wt%, shows an initial efficiency of 95%, a 100-cycle 1C capacity retention of 90.6%, and a full-charge expansion of 59%. This indicates that the expansion suppression of the anode material of this invention decreases with increasing silicon content. Example 6, with a silicon content of 39wt%, shows an initial efficiency of 92.4%, a 100-cycle 1C capacity retention of 92.8%, and a full-charge expansion of 58%, demonstrating that the coating layer can further improve interface stability without compromising the geometric synergistic constraint of this invention.

[0123] Comparative Example 1 (R) c =4.0) and Comparative Example 2 (λ) Si / λ C =0.43) Cycle retention drops to 41% and 58%, while expansion rises to 85% and 42%, confirming the invention's t w t Si R c , λ Si , λ C The synergistic effect. Furthermore, comparative example 3 (λ) C =50nm) Due to the excessively large carbon domains, the flexibility is insufficient, and the cycle retention rate drops to 60%, while the full charge expansion rate rises to 57%, and the 5C rate retention rate is only 55%; Comparative Example 4 (t w Although the silicon domain spacing λ (25 nm) is stable during cycling (95% retention, only 12% expansion), its specific capacity is only about 300 mAh / g and its 5C rate retention is only 45% due to its extremely low silicon loading and thick walls that hinder lithium-ion transport. Both of these factors, namely excessively large carbon domains and excessively thick pore walls, confirm the existence of the silicon domain spacing λ in this invention.Si Carbon domain size λ C The necessity of.

[0124] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A silicon-carbon composite material for a lithium-ion battery negative electrode, characterized in that, The composite material, comprising a porous carbon framework and silicon deposited on the inner surface of the pore walls of the porous carbon framework, satisfies the following conditions: (a) Confinement ratio R c =t Si / t w Satisfying 0.05≤R c ≤0.9; Among them, t w The equivalent pore wall thickness refers to the average thickness of the solid carbon wall between adjacent pores; t Si Equivalent silicon film thickness refers to the average thickness of the silicon layer deposited on the inner surface of the hole wall; (b) Silicon domain spacing λ Si , satisfying 1≤λ Si ≤200nm, the λ Si The average Euclidean distance between the centroids of adjacent silicon enrichment domains; (c) Carbon domain size λ C The condition 0.35 ≤ λ is satisfied. C ≤40nm, the λ C The characteristic size of graphite-like coherent domains in the carbon framework; The silicon domain spacing and carbon domain size satisfy λ. Si / λ C ≥1.5, and the equivalent pore wall thickness and carbon domain size satisfy 0.5≤t w / λ C ≤1.

2. The silicon-carbon composite material according to claim 1, characterized in that, The equivalent hole wall thickness t w The thickness is 1~20nm; And / or, the equivalent silicon film thickness t Si The thickness is 0.5~12nm.

3. The silicon-carbon composite material according to claim 1, characterized in that, The raw materials for preparing the porous carbon framework are selected from at least one of hard carbon, soft carbon, mesoporous carbon, biomass-derived carbon, resin-derived carbon, pitch-derived carbon, graphite, and Ketjen black. And / or, the specific surface area of ​​the porous carbon framework is 50 m² / g to 2500 m² / g, and the pore volume is 0.2 cm³ / g to 3.0 cm³ / g.

4. The silicon-carbon composite material according to claim 1, characterized in that, The silicon-carbon composite material contains 5 wt% to 90 wt% silicon by mass. And / or, the silicon-carbon composite material further includes a doping element selected from at least one of N, B, P, O, S, F, Al, Ti, Mg, Ca and transition metals.

5. The silicon-carbon composite material according to claim 1, characterized in that, The outer surface of the porous carbon skeleton is also covered with a coating layer; And / or, the thickness of the coating layer is 0.5~50nm; And / or, the coating layer is a carbon coating layer, which is an amorphous carbon layer, a graphitized carbon layer, or a composite layer of both.

6. A method for preparing a silicon-carbon composite material according to any one of claims 1 to 5, characterized in that, The preparation method includes: (A) Provide a porous carbon framework, and then place the porous carbon framework in a closed reactor and introduce a mixture of silicon precursor gas; (B) At a deposition temperature of 300~700℃, silicon is deposited on the inner surface of the pore walls of the porous carbon framework by chemical vapor deposition. The chemical deposition conditions are controlled so that the resulting silicon-carbon composite material satisfies: 0.05≤R c ≤0.9, 1≤λ Si ≤200nm, 0.35≤λ C ≤40nm, λ Si / λ C ≥1.5 and 0.5≤t w / λ C ≤1.

7. The preparation method according to claim 6, characterized in that, The silicon-containing precursor mixed gas in (A) is formed by mixing the silicon-containing precursor with a carrier gas; And / or, the silicon-containing precursor is selected from one or more of silane, dichlorosilane, trichlorosilane, and silicon tetrachloride; And / or, the carrier gas is an inert gas, preferably Ar or N2; And / or, the volume fraction of the silicon-containing precursor in the silicon-containing precursor mixture is 5% to 40%, and the system pressure is 10 to 110 kPa.

8. The preparation method according to claim 6, characterized in that, The chemical vapor deposition is performed using a segmented temperature control method, including the following steps: First stage: Heat the reactor to 500~650℃, introduce a mixed gas containing silicon precursor, and deposit for 10~60 min under 80~101kPa conditions; Second stage: Cool the reactor to 400~500℃, reduce the system pressure to 10~50kPa, and deposit for 30~120min; The third stage: Heat the reactor to 550~700℃ and anneal it under an inert atmosphere for 30~120 minutes.

9. A lithium-ion battery negative electrode sheet, characterized in that, It includes a current collector and a negative electrode active material layer coated on the surface of the current collector, wherein the negative electrode active material layer comprises the silicon-carbon composite material according to any one of claims 1 to 5, a binder, and an optional conductive agent.

10. A lithium-ion battery, characterized in that, It includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode is the lithium-ion battery negative electrode sheet according to claim 9.